Etymology in the Polish Academy of Sciences Great Dictionary of Polish - Dębowiak, Przemysław; Ostrowski, Bogumił; Waniakowa, Jadwiga (Lexikos, 2017)
The article offers an insight into etymological information provided in the Polish Academy of Sciences Great Dictionary of Polish (Pol. Wielki sÅ‚ownik jÄ™zyka polskiego PAN, WSJP PAN). The dictionary and the rules of producing the entries are briefly presented. These rules influence the way of working on etymology within the project. The main part of the article is devoted to the presentation of the field relating to origin and the etymological information which is given in one-word entries. The principles of elaborating upon this information in the dictionary are presented in detail and illustrated with examples. Moreover, some problems, like the question of borrowings, calques and semantic motivation, are discussed in the paper as well.